ANALISIS PENERIMAAN PAJAK BUMI DAN BANGUNAN (PBB) DI DUA DESA DI KECAMATAN TIRTAYASA KABUPATEN SERANG - Nofia Laser; Rahmat Yuliadi (Universitas Serang Raya, 2014)
In conducting this study, the authors use the method of comparative research is a method of collecting, presenting and comparing two or more samples so that the resulting picture of the land and building tax on Tirtayasa District District of attack, so this study focused on land and building tax revenue contained in the Village Tirtayasa and Village Sujung, so knowing there a difference in land and building tax revenue. It can be influenced by the low level of public awareness that will tax, education level, income level, and high levels of welfare. Thus weakening the level of awareness of the importance of the tax would prove to the tax rate that can be described through the acceptance and realization of the Tax Years 2007 through 2011 are still far from increasing. Acceptance of Land and Building Tax (PBB) in the Village and Village Sujung Tirtayasa obvious the difference between tax assessment and realization, acceptance of land and building tax (PBB) Ds. Tirtayasa reached 100% while the Ds. Sujung not meet the target. The government should hold frequent socialization Land and Building Tax (PBB) on society. Keywords : Land and Building Tax, The government, Revenue